(untitled) (PETITUM, 2022)
ABSTRACT: The purpose of this study is to analyze the absolute authority of the State Administrative Court and the General Court in issuing land rights and to find out and analyze the considerations of the Makassar State Administrative Court Panel of Judges regarding the absolute authority of Decision Number: 118/G/2019/PTUN.MKS. This research is normative legal research. The results of this study indicate that: (1). Ownership, in this case, differences in the history of land origin, then becomes the competence of the General Court so as to emphasize that what is the authority of a certain judicial body cannot become the authority of other judicial bodies. (2). The Defendant’s exception to the decision Number: 118/G/2019/PTUN.MKS, was accepted resulting in a formal defect in the lawsuit so that the lawsuit was not accepted because it has not considered the subject matter of the case/dispute at all. ABSTRAK: Tujuan Penelitian menganalisis kewenangan absolut Peradilan Tata Usaha Negara dan Peradilan Umum dalam penerbitan hak atas tanah dan untuk mengetahui dan menganalisis pertimbangan Majelis Hakim PTUN Makassar terkait kewenangan absolut Putusan Nomor: 118/G/2019/PTUN.MKS. Penelitian ini adalah penelitian hukum normatif,. Hasil Penelitian ini menunjukkan bahwa : (1). Kepemilikan dalam hal ini perbedaan riwayat asal tanah maka menjadi kompetensi Peradilan Umum sehingga dengan demikian menegaskan apa yang menjadi kewenangan suatu badan peradilan tertentu tidak dapat menjadi kewenangan badan peradilan lainnya. (2). Eksepsi Tergugat pada putusan Nomor: 118/G/2019/PTUN.MKS, diterima sehingga mengakibatkan cacat formil dari gugatan sehingga gugatan tidak diterima oleh karena itu sama sekali belum mempertimbangkan materi pokok perkara/sengketa.